PENGARUH CUSTOMER VALUE, CUSTOMER EXPERIENCE, DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN - Harsen Subakti; Ratnawili Ratnawili (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
Customer loyalty is one of the key elements in business sustainability in an increasingly competitive and dynamic market. The aim of this study is to determine whether Customer Value, Customer Experience, and Customer Trust have a positive effect on Customer Loyalty (Case Study on Consumers of Jhon Motor Workshop Padang Jati, Bengkulu City). This research uses a quantitative approach. The sampling in this study was carried out using a total sampling method with a sample size of 95 customers. The researcher used questionnaire and documentation data collection techniques. The results of the study show that (1) Customer Value has a positive effect on customer loyalty at Jhon Motor Workshop Padang Jati with a significance value of 0.000 < 0.05 and t count > t table or 6.635 > 1.669; (2) Customer experience has a negative effect on customer loyalty at Jhon Motor Padang Jati workshop with a significance value of 0.005 < 0.05 and calculated t > table t or 4.490 > 1.669; (3) Customer trust has a negative effect on customer loyalty at Jhon Motor Padang Jati workshop with a significance value of 0.002 < 0.05 and calculated t > table t or 4.415 > 1.669; (4) Customer Value, Customer experience, and Customer trust have a positive effect on customer loyalty at Jhon Motor Padang Jati workshop with a significance value of 0.000 < 0.05. These research results can provide input for service business actors, such as workshops, in improving service quality through understanding customer behavior.  Keywords: Customer Loyalty, Customer Value, Customer Experience, and Customer Trust